IDENTIFIKASI ETNIS MAYBRAT DI KABUPATEN MAYBRAT PROVINSI PAPUA BARAT - Mora, Fersyd D.; Wambrauw, Hengky L. (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2018)
This study aims to identify and describe the social group called ethnic Maybrat in Maybrat Regency, Papua Province in the socio-cultural system in the archipelago’s cultural treasures. This research was carried out using a qualitativedescriptive method of variables which included: genealogy of the origin of tribes, meaning of clan and area of distribution, land and markers of communal rights, customary rights boundaries, symbols, local languages, interaction with other local tribes, views and philosophy, land, and so on. The approach used in this study is ethics and emic. The ethical approach includes fndings that appear consistent or permanent in various cultures, in other words an ethic refers to the truth or universal principles. Whereas emik on the contrary, refers to fndings that look different for different cultures, thus, an emik refers to a culture-specifc truth. The results of the study include the following: (a) historical ﬂashes, (b) characteristics and distribution, (c) livelihood systems, (d) labor division systems, (e) sacred zoning systems, (f) trading systems, ( g) belief systems, (h) technology systems, (i) traditional leadership systems, and (j) social stratifcation systems.